1999
DOI: 10.1080/00288233.1999.9513348
|View full text |Cite
|
Sign up to set email alerts
|

Temperature responses and nuclear DNA amounts of seven white clover populations which differ in early spring growth rates

Abstract: The growth of seven white clover populations differing in morphology, geographic origin, and seasonality of growth was measured at constant temperatures ranging from 5°C to 25°C in controlled environment chambers. All populations showed increased growth up to a maximum of 20-25°C, but there were significant shifts in the relative performance of the populations at different temperatures. Leaf appearance rates, leaf sizes, and stolon extension rates were all differentially affected by temperature. Growth potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Those that grew early in the spring had larger GS (here recorded as a negative correlation with temperature, Table 2.). Campbell et al (1999) found the same correlation for populations of white clover. However, Bretagnolle and Thompson (1996) found the opposite relationship for sympatric Dactylis glomerata populations.…”
Section: E C O L O G Ysupporting
confidence: 54%
“…Those that grew early in the spring had larger GS (here recorded as a negative correlation with temperature, Table 2.). Campbell et al (1999) found the same correlation for populations of white clover. However, Bretagnolle and Thompson (1996) found the opposite relationship for sympatric Dactylis glomerata populations.…”
Section: E C O L O G Ysupporting
confidence: 54%
“…Restoration of photosynthetic capacity and metabolic activity is an important factor in low temperature acclimation of white clover and herbaceous winter annuals (Woledge and Dennis, 1982;Woledge et al, 1989;Hurry et al, 1995). Although leaf emergence is strongly temperature dependent (Haycock, 1981;Eagles and Othman, 1988;Campbell et al, 1999;Corbel et al, 1999), the present results suggest that cultivars that produce leaves at low temperatures are at a considerable advantage compared with cultivars with a higher temperature threshold for leaf emergence.…”
Section: Dynamics Of' Leaf Turnover and Significance Of The Cultivarmentioning
confidence: 55%
“…The number of leaves that emerged during winter, and the increase in the rate of leaf emergence per temperature increment, were clearly higher for AberHerald than for Grasslands Huia, although the temperature threshold (2.9 C) for leaf emergence was the same for both cultivars and was similar to that reported by Haycock (1981). Similarly, the experiments of Corbel et al (1999) showed a significantly smaller decrease in the rate of leaf emergence of AberHerald compared with Grasslands Huia after chilling at 5 C. A comparative study with seven white clover cultivars showed that temperature had a stronger effect on plant growth during winter and spring than during the growing season, and that the capacity for growth at 5 C was important for the success of several white clover populations in the late winter and early spring (Campbell et al, 1999). In the experiment conducted by Campbell et al (1999), Grasslands Huia had the highest rate of leaf emergence at 5 C of the seven cultivars tested.…”
Section: Dynamics Of' Leaf Turnover and Significance Of The Cultivarmentioning
confidence: 85%
See 1 more Smart Citation
“…Trifolium repens L. var. 'Grasslands Huia' was used as the standard as it was known to have a 2C-value of 2.38 picograms (pg) (Campbell et al 1999). For each sample, a leaf segment of this reference tissue was co-chopped with the test sample, and the ratio of the test sample to the standard peak channel was used to compute the 2C-values for each test sample.…”
Section: Methodsmentioning
confidence: 99%